Inter-hospital variations in caesarean sections. A risk adjusted comparison in the Valencia public hospitals. Issue 8 (1st August 2000) - Librero, Julian; Peiró, Salvador; Calderón, Soledad Márquez
Abstract : BACKGROUND: The aim of this study was to describe the variability in caesarean rates in the public hospitals in the Valencia Region, Spain, and to analyse the association between caesarean sections and clinical and extra-clinical factors. METHODS: Analysis of data contained in the Minimum Basic Data Set (MBDS) compiled for all births in 11 public hospitals in Valencia during 1994–1995 (n=36 819). Bivariate and multivariate analyses were used to evaluate the association between caesarean section rates and specific risk factors. The multivariate model was used to construct predictions about caesarean rates for each hospital, for comparison with rates observed. RESULTS: Caesarean rates were 17.6% (inter-hospital range: 14.7% to 25.0%), with ample variability between hospitals in the diagnosis of maternal-fetal risk factors (particularly dystocia and fetal distress), and the indication for caesarean in the presence of these factors. Multivariate analysis showed that maternal-fetal risk factors correlated strongly with caesarean section, although extra-clinical factors, such as the day of the week, also correlated positively. After adjusting for the risk factors, the inter-hospital variation in caesarean rates persisted. CONCLUSIONS: Although certain limitations (imprecision of some diagnoses and information biases in the MBDS) make it impossible to establish unequivocal conclusions, results show a high degree of variability among hospitals when opting for caesarean section. This variability cannot be justified by differences in obstetric risks.